2008
DOI: 10.1063/1.2828496
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between primary and secondary Johari–Goldstein relaxations in supercooled liquids: Invariance to changes in thermodynamic conditions

Abstract: The primary alpha and the secondary Johari-Goldstein (JG) beta relaxations of supercooled glass-forming neat epoxy resin and 2-picoline in mixture with tristyrene are monitored by broadband dielectric relaxation spectroscopy at ambient pressure and elevated pressures. For different combinations of pressure and temperature that maintain the alpha-relaxation time constant, the frequency dispersion of the alpha relaxation is unchanged, as previously found in other glass-formers, but remarkably the JG beta-relaxat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
182
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(194 citation statements)
references
References 18 publications
12
182
0
Order By: Relevance
“…Several previous experimental studies [15,16,[18][19][20][21][22] and simulations have verified two simultaneous CM predictions in mixtures where the host has a significantly higher T g than the guest. They are:…”
mentioning
confidence: 69%
See 3 more Smart Citations
“…Several previous experimental studies [15,16,[18][19][20][21][22] and simulations have verified two simultaneous CM predictions in mixtures where the host has a significantly higher T g than the guest. They are:…”
mentioning
confidence: 69%
“…Remarkably, the connection is passed onto the α-and JG β-relaxations of a component in mixtures of two van der Waals glass-formers. An example is the invariance of the ratio of τ αg to τ JG,g , the relaxation time of the JG β-relaxation, to widely different combinations of pressure and temperature that maintain τ α,g constant [15][16]. This is a remarkable result because in these experiments the specific volume varies over a significant range, and yet τ αg /τ JG,g is invariant at constant τ αg .…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…31 The frequency separation between the α relaxation process and such secondary relaxation has been shown to be invariant under isochronal conditions within the temperature-pressure diagram. 32 These studies have thus concluded that the EW is a "precursor" Johari Goldstein relaxation, as shown e.g. for the case of glycerol, 31 ethanol, 17 and propylene glycol oligomers.…”
Section: Introductionmentioning
confidence: 99%